Development of a water cooling system for Nd:YAG Laser Chamber - Azahari, Nor Aziawati (2005)
In solid state lasers, only a small fraction of electrical input power is converted to laser radiation. The remainder of the input power is converted to heat. Therefore, solid state lasers require cooling for the pump source and active medium. In the case of flashlamp pumping usage, a cooling system in the chamber is desirable. Without adequate cooling, the laser seals, pumping cavity, lamps and the rod itself would be damaged by overheating. Thus, the aim of this project is to develop a water cooling system such that the lowest practical operating temperature is produced, and to monitor temperatures of the laser chamber during the pumping process. In order to achieve these objectives, a refrigerated water cooling system was developed which included an internal and external water cooling system. Measurements of various parameters of this water cooling system were made in order to determine its appropriateness in solid state laser chamber. A laser chamber was set-up, which comprised of a Nd:YAG laser rod, flashlamp, chamber heat sink and stainless steel blocks. An aluminium laser house was designed inclusive with electrical and water piping system. After assembling the whole system, the circulation of water in the cooling system was tested. This is to ensure no leakage occurred during the pumping process. The flow rate of water during circulation is 9.83 Â± 0.01 liter / min. The minimum temperature of the cooling system that could be achieved was 18.00 Â± 0.05 oC. The temperature distribution during pumping process was monitored at different points on the laser chamber. The information obtained leads to the calculation of heat dissipation from the laser chamber which operated with and without chilled distilled water. The comparison results shows that 20% improvement in heat liberated from flashlamp, whereas, 90% and 86% improvement in heat absorption in chamber heat sink and stainless steel blocks respectively. This indicated that the cooling system provided in the laser chamber was very effective in carrying out the excess heat from pumping process.